Studies on the paramyxovirus accessory genes by reverse genetics in the Sendai virus–mouse system - Sakaguchi, Takemasa (The Japan Academy, 2008)
Nucleotide sequencing of the entire genomes was completed in the 1980s for most members of the Paramyxoviridae. It then became a new common task with challenge for researchers in the field to establish a system to recover the virus entirely from cDNA, thereby allowing reverse genetics (free manipulation of the viral genome). Using Sendai virus, we established a system of incomparable virus recovery efficiency early on. This technology was then fully exploited in answering a series of long-held questions. In particular, two accessory genes whose functions had remained enigmatic were demonstrated to encode special functions critical in viral in vivo pathogenesis producing fatal pneumonia in mice, although dispensable in virus replication at the in vitro cellular level. Their in vivo functions were found to counteract the two respective facets of the antiviral state induced by interferons and an interferon regulatory factor 3-dependent but yet unknown effector. These achievements appear to have facilitated a scientific trend where the accessory genes are a focus of active investigation in studies on other paramyxoviruses and opened up a new common ground shared between virology and immunology.